2020
DOI: 10.1148/radiol.2020200236
|View full text |Cite
|
Sign up to set email alerts
|

CT Imaging of the 2019 Novel Coronavirus (2019-nCoV) Pneumonia

Abstract: On the basis of epidemiologic characteristics, clinical manifestations, chest images, and laboratory findings, the diagnosis of 2019-nCoV pneumonia was made. After receiving 3 days of treatment, combined with interferon inhalation, the patient was clinically worse with progressive pulmonary opacities found at repeat chest CT (Figure, B). Disclosures of Conflicts of Interest: J. Lei disclosed no relevant relationships. J. Li disclosed no relevant relationships. X.L. disclosed no relevant relationships. X.Q. dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
530
1
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 634 publications
(604 citation statements)
references
References 2 publications
46
530
1
17
Order By: Relevance
“…One of the COVID-19 case reports showed a patient at 5 days of fever presented with a cough, coarse breathing sounds of both lungs, and a body temperature of 39.0°C. The patient's sputum showed positive real-time polymerase chain reaction results that confirmed COVID-19 infection [14]. The laboratory studies showed leucopenia with leukocyte counts of 2.91 × 10^9 cells/L of which 70.0% were neutrophils.…”
Section: Pathogenesismentioning
confidence: 79%
See 3 more Smart Citations
“…One of the COVID-19 case reports showed a patient at 5 days of fever presented with a cough, coarse breathing sounds of both lungs, and a body temperature of 39.0°C. The patient's sputum showed positive real-time polymerase chain reaction results that confirmed COVID-19 infection [14]. The laboratory studies showed leucopenia with leukocyte counts of 2.91 × 10^9 cells/L of which 70.0% were neutrophils.…”
Section: Pathogenesismentioning
confidence: 79%
“…Additionally, a value of 16.16 mg/L of blood C-reactive protein was noted which is above the normal range (0-10 mg/L). High erythrocyte sedimentation rate and D-dimer were also observed [14]. The main pathogenesis of COVID-19 infection as a respiratory system targeting virus was severe pneumonia, RNAaemia, combined with the incidence of ground-glass opacities, and acute cardiac injury [6].…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In the progressive phase, most of the COVID-19 lesions progressed rapidly, and corresponded to the severe type clinical classification. Compared to the early stage, the number of lesions increased significantly, with the extent and density of the lesions increasing concurrently (16,17) (Fig. 6).…”
Section: Radiological Manifestationsmentioning
confidence: 91%